The Effectiveness of Project-Based Learning Models in Improving Students' Creativity (A Literature Review) - Cahyani, Ni Ketut Cendy (STKIP AGAMA HINDU SINGARAJA, 2021)
The learning process on the 2013 curriculum uses a scientific approach that emphasizes students' activity in learning (student-centered learning). Learning that uses a scientific approach needs to be supported by the appropriate model and method. Project-based learning is one of the suggested learning models in the 2013 curriculum (K13). This learning model is designed to engage students in investigating real-world problems in their learning. Project-based learning drives teaching and learning, involves students in the learning process, motivates, and enhances the creativity of students. Hence, project-based learning is the appropriate learning model to improve students' creativity because it requires the students to be directly involved in their learning. Besides, students will also be more interested in learning because the problems used are related to their environment. Thus, the purpose of this paper is sharing the effectiveness of project-based learning model in improving students' creativity.